Cities at Sea: Coastal Urbanization Generates Local Biodiversity Hotspots but Homogenizes Marine Fish Communities Regionally - Bastien Macé; Erwan Delrieu‐Trottin; David Mouillot; Alice Valentini; Morgane Bruno; Laure Velez; Amandine Avouac; Julie Deter; Thomas Bockel; Marie Orblin; Pierre Boissery; Gwénolé Le Roux; et al. (Global Change Biology, 2026)
Urbanization is rapidly expanding along the world's coasts, transforming natural ecosystems into increasingly uniform artificial environments. Yet, the patterns and processes shaping marine biodiversity under urban pressure remain poorly understood. We investigated whether coastal urbanization drives marine communities toward greater similarity, a process well documented in terrestrial and freshwater systems as urban biotic homogenization but rarely examined in the sea. We analyzed fish communities using 222 seawater environmental DNA samples collected across Mediterranean seaports and less urbanized coastal sites. Seaports exhibited higher local species richness than less urbanized sites, yet their communities were markedly more similar to one another, revealing a local‐regional decoupling paradox in which gains in local diversity coincided with biotic homogenization at the regional scale. This pattern emerged in the absence of non‐indigenous species, which are commonly invoked as main drivers of homogenization. Instead, homogenization was primarily driven by increased occupancy (i.e., the proportion of sites occupied) of disturbance‐tolerant native taxa, half of which showed occupancy levels approximately 2.6 times higher in seaports than elsewhere. Biotic homogenization was evident at both taxonomic and phylogenetic levels, indicating that disturbance‐tolerant taxa are phylogenetically clustered. Overall, urban pressure emerged as the dominant driver of community similarity, exceeding spatial and environmental predictors. Together, these results show that coastal urbanization emerges as a fundamental and underappreciated driver of marine biodiversity reorganization.